2013
DOI: 10.1097/ncc.0b013e318291b4e9
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Young Adult Cancer Patients Described Through Online Narratives

Abstract: Blogs can be particularly helpful when patients are isolated or physically unable to interact with other people because of treatment requirements or physical deterioration.Future studies should investigate other types of Internet cancer communities and how they can benefit the development of Internet-based support networks for YAACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…Cancer and its treatment can impede cognitive maturation and performance for young adults (aged 20-29 years) 23 and thus capacity to make complex medical decisions, perform at school or work, and achieve vocational goals. 6 The gravity of a cancer diagnosis, uncertainty about the future, and low energy levels can thwart planning related to vocational goals.…”
Section: Developmentalmentioning
confidence: 99%
“…Cancer and its treatment can impede cognitive maturation and performance for young adults (aged 20-29 years) 23 and thus capacity to make complex medical decisions, perform at school or work, and achieve vocational goals. 6 The gravity of a cancer diagnosis, uncertainty about the future, and low energy levels can thwart planning related to vocational goals.…”
Section: Developmentalmentioning
confidence: 99%
“…845 Beginning in 2008, 46 researchers also began analyzing the use and content of blogs and blog responses, often examining reasons for and benefits of blogging during cancer treatment and survivorship (n = 7; 10.1%). 4652 Published studies also specifically addressed cancer-related use of video-sharing sites such as YouTube (n = 5; 7.2%), 5357 and social networking sites such as Facebook (n = 8; 11.6%). 5865 …”
Section: Resultsmentioning
confidence: 99%
“…In Part 1, findings showed a rich description of the lived experiences of YAACs while exploring their unique needs and difficulties associated with their transition from adolescence to adulthood. 4 Part 1 also reported that blogs provide an environment where YAACs can express their emotions with fewer inhibitions. 4 This article, Part 2, examines whether there is a gender-based difference influencing the expression of experiences and emotions when blogs are used.…”
Section: Blogs and Cancer Patients And Gender Differencesmentioning
confidence: 94%
“…4 Part 1 also reported that blogs provide an environment where YAACs can express their emotions with fewer inhibitions. 4 This article, Part 2, examines whether there is a gender-based difference influencing the expression of experiences and emotions when blogs are used. Numerous psychosocial oncology research studies have investigated how gender affects cancer patients' experiences.…”
Section: Blogs and Cancer Patients And Gender Differencesmentioning
confidence: 94%